Analysis of duo mobile application on enhancing user authentication in cloud computing / Nor Fazalina Azman - Azman, Nor Fazalina
Cloud computing is an IT service that can access remotely at any time and from anywhere through the internet. In order to secure data stored in the cloud, an efficient authentication method must be considered to overcome the security concerns. This project proposed the used of duo mobile application software as a second layer of authentication and the application is installed in the mobile device prior to login to the web page. The proposed technique is proven to mitigate few types of attacks such as Man-in-the-Middle (MTTM) and session cookies stolen.